Comparison between Biological Activities of Commercial and Synthesized Carbon Nanotubes by Flame Fragments Deposition Technique (Baghdad Science Journal, 2019)
Carbon nanotubes (CNTs) were synthesized via liquefied petroleum gas (LPG) as precursor using flame fragments deposition (FFD) technique. In vitro, biological activates of carbon nanotubes (CNTs) synthesized by FFD technique were investigated. The physiochemical characterizations of synthesized CNTs are similar to other synthesized CNTs and to the standard sample. Pharmaceutical application of synthesized CNTs was studied via conjugation and adsorption with different types of medicines as promote groups. The conjugation of CNTs was performed by adsorption the drugs such as sulfamethoxazole (SMX) and trimethoprim (TMP) on CNTs depending on physical properties of both bonded parts. The synthesized CNTs almost have the same performance in antibiotic activity compared with standard sample of CNTs (commercial CNTs).The products were effective antibiotic in the treatment as resistant bacteria, may higher concentration of CNTs would have antibacterial activity on multi-drug resistant bacteria such as Acinetobacter and also on resistant E.coli. The bioactivity synthesized and standard samples of CNTs were almost the same against different types of bacteria.